Digital health and modern technologies applied in patients with heart failure: Can we support patients’ psychosocial well-being? - Uchmanowicz, Izabella; Wleklik, Marta; Foster, Marva; Olchowska-Kotala, Agnieszka; Vellone, Ercole; Kaluzna-Oleksy, Marta; Szczepanowski, Remigiusz; Uchmanowicz, Bartosz; Reczuch, Krzysztof; Jankowska, Ewa Anita (Frontiers in Psychology, 2022)
Despite advances in the treatment of heart failure (HF), the physical symptoms and stress of the disease continue to negatively impact patients' health outcomes. Technology now offers promising ways to integrate personalized support from health care professionals via a variety of platforms. Digital health technology solutions using mobile devices or those that allow remote patient monitoring are potentially more cost effective and may replace in-person interaction. Notably, digital health methods may not only improve clinical outcomes but may also improve the psycho-social status of HF patients. Using digital health to address biopsychosocial variables, including elements of the person and their context is valuable when considering chronic illness and HF in particular, given the multiple, cross-level factors affecting chronic illness clinical management needed for HF self-care.